Isomorphism and Firm Performance in the UK House Building Industry, 1999-2013 - Meyer, Andreas P. (2014)
Isomorphism or strategic homogeneity within organisational fields is a widely observed phenomenon and, thus, a relevant topic for management theorists and practitioners (Huff, 1982; Oliver, 1997a). This study attempts to establish support for a negative relationship between isomorphism and firm efficiency and performance, as suggested by DiMaggio and Powell (1983). The longitudinal, multiple-case study (Eisenhardt, 1989) of eight UK house builders between 1999 and 2013 finds that isomorphism might have negatively affected the performance of the UK house builders during the crisis in 2007/2008. Moreover, the findings suggest that the performance decline might have been prevented by rejecting volume growth orientated strategies and by reacting more sensitively to the approaching economic downturn. The study contributes to institutional theory and the understanding of the dangers of isomorphism and strategic homogeneity in a highly cyclical industry in the extreme case of an economic crisis.